2018
DOI: 10.1061/(asce)co.1943-7862.0001525
|View full text |Cite
|
Sign up to set email alerts
|

Procurement and Governance Choices for Collaborative Infrastructure Projects

Abstract: 21Collaborative approaches to infrastructure procurement are increasingly popular around the 22 42 team selection, although the specific actions recommended vary. 44Author keywords 45 46

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
34
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(40 citation statements)
references
References 27 publications
3
34
0
Order By: Relevance
“…Furthermore, our interviewees underlined the importance of determining clear targets for collaboration and the respective responsibilities which resonates with the literature highlighting the development of clear and precise risk and reward schemes (Chen et al, 2018;Suprapto et al, 2015). It needs to be noted that targets do not have to be determined at the contractual level; rather, each organization and especially investors have to have a clear view on what is pursued through using collaborative practices in project management.…”
Section: Discussionsupporting
confidence: 56%
See 2 more Smart Citations
“…Furthermore, our interviewees underlined the importance of determining clear targets for collaboration and the respective responsibilities which resonates with the literature highlighting the development of clear and precise risk and reward schemes (Chen et al, 2018;Suprapto et al, 2015). It needs to be noted that targets do not have to be determined at the contractual level; rather, each organization and especially investors have to have a clear view on what is pursued through using collaborative practices in project management.…”
Section: Discussionsupporting
confidence: 56%
“…An organizational system in a project consists of people, teams, organizational units, etc., which undertake the work that is related to each other through mechanisms such as communication (Browning et al, 2006) . r n a t i o n a l J o u r n a l o f M a n a g i n g P r o j e c t s i n B u s i n e s s The literature on inter-organizational collaboration stresses the importance of themes such as trust (Dietrich et al, 2010;Haaskhold et al, 2020), trust-control balance (Walker et al, 2017), relationship programs (Aaltonen and Turkulainen, 2018), culture of collaboration (Aarseth and Sorhaug, 2009) and focus on team formation (Lahdenperä, 2012;Oraee et al, 2017) or teamwork in general (Chen et al, 2018;Oraee et al, 2017;Suprapto et al, 2015). Yet, focusing too much on relationship development and embeddedness may also lead to the realizations of the dark sides of collaborative relationships.…”
Section: Inter-organizational Collaboration In Projectsmentioning
confidence: 99%
See 1 more Smart Citation
“…The successful implementation of a CPDM is based on social relationships between project actors, as the model builds on trust, enabling the sharing of resources and processes (Lahdenper€ a 2012, Hietaj€ arvi 2017). CPDMs consist of both contractual mechanisms and non-contractual mechanisms like leadership, collaboration, communication and integration of resources and processes (Chen et al 2018).…”
Section: Collaborative Project Delivery Models In Infrastructure Constructionmentioning
confidence: 99%
“…From the data, we found that as a project progresses, the ties between actors start to shape the project network. Project governance is based on both formal ties, such as contracts (Adami and Verschoore 2018) and project organization, but also on informal, social ties (Chen et al 2018, Pryke et al 2018. Formal ties impact the collaboration within the project network and the organization in the initial phases, while the influence of informal ties begins at the later phases, during project delivery.…”
Section: The Role Of Social Ties In Cpdmmentioning
confidence: 99%